Makna Berjilbab Bagi Muslimah Management Jilbab Clemira di Ujung Berung Bandung - Manzilla Khoerunnisa (International Journal Labs, 2022)
In this research, it started from the existence of phenomena that are developing at this time. Religious diversity exists in today's society. But with the diversity of thoughts in religion, it is able to foster visions and solutions that can create an understanding of the meanings in religion. The phenomenon of hijab is a phenomenon that is rife in this modern era, the kinds of hijab and its uses for Muslim women. With this phenomenon, many communities have created several talents to show their style and compete about what they want to achieve. This study aims to conclude a diversity that exists in society about the laws that have been agreed upon by Islam. In this study, it has used methods such as descriptive qualitative with reference to this research using the data collection techniques used, namely in the form of observations in it as well as interviews with several sources and documentation. In this study, it is supported by a phenomenological approach, because the approach is related and able to show appropriate results in this study. Several methods can also help complete this research. In this study, researchers also expect the public to understand various rules or sharia that exist in Islam.